The Influence Of Sand Casting Mold Solidfication Pressure Variations To The Quality Of Al-Si Alloy Casting Product - Aprianur Fajri; Basyirun Basyirun (JMES: The International Journal of Mechanical Engineering and Sciences, 2018)
The purpose of this study is to find The influence of the sand cast solidification pressure variations to the quality of an alloy Al-Si casting product. An experimental method was used in the study and the analysis of the data used descriptive analysis to explain the charts. The stages of researched process is preparation material and equipment; making the design and manufacture of a pattern; manufacture of the sand mold by 35, 40, 45, 50, and 55 kg/cm2 pressure variation; casting process; observation of defect; measurement of the level roughness; microstructure examination; assay composition; and last test is hardness micro vickers test. The research results show that variations pressure 35 kg/cm2 does not occur defect the needle at al. A defect of the needle that occur most frequently upon variations of the pressure of the 55 kg/cm2 is as much as 0.62 % . Air cavities formed to variation pressure solidification 35 kg/cm2 of 0.77 % to the least, while in variation 55 kg/cm2 happened the number of defect air cavities the most namely 3.96 % . The mold fall defect largest namely 1.95 % happened to variation pressure 35 kg/cm2. Defect of sand inclusion the least of 0.06 % happened to variation pressure 55 kg/cm2. Defect of fins formed due to variation pressure solidification sand mold experienced the number of been fluctuating, recorded high in early then decline and to high back in highest variation. The pressure variation 35 kg/cm2 it has value roughness flattened 3.17 and products castings the most rough happened to sand mold solidification variation pressure 55 kg/cm2 , with on average of 5.44. the degree of hardness highest of 141.8 VHN happened to variation pressure 35 kg/cm2 and lowest of 124.8 VHN happened to variation 55 kg/cm2. Concluded that the solidification of pressure variations sand mold 45 kg / cm2 produce castings products with the most optimal average in terms of the measurement of the defective; variation pressure solidification sand mold of sand casting 35 kg / cm2 produce a smooth surface, and the higher pressure make surface castings becomes rougher; solidification of pressure variations and coarse sand mold 35 kg / cm2 produce micro structure with smooth grains and becomes more violent along with increasing pressure; pressure variation 35 kg / cm2 produce a hardest surface, the higher of the pressure variation it becoming violence number progressively lower.